ДАСТУРЛАШГА ОИД ФАННИ ЎҚИТИШ ВА БАҲОЛАШГА МЎЛЖАЛЛАНГАН ТИЗИМНИНГ ДАСТУРИЙ ТАЪМИНОТИ - Абдукаримов, С.С. (SCIENCE and SOCIETY, 2021)
The paper considers automatic testing system, its functionality, types of results and evaluating students’ knowledge using the system. Furthermore, ways of marking students in the system is analysed.